Exercise load and physical activity intensity in relation to dystonia and choreoathetosis during powered wheelchair mobility in children and youth with dyskinetic cerebral palsy. Issue 17 (14th August 2022) - Bekteshi, Saranda; Nica, Ioana Gabriela; Gakopoulos, Sotirios; Konings, Marco; Maes, Rozanne; Cuyvers, Benoit; Aerts, Jean-Marie; Hallez, Hans; Monbaliu, Elegast
Abstract: Purpose: To explore the relation between exercise load, physical activity intensity, and movement disorders during powered wheelchair (PW) mobility in people with severe dyskinetic cerebral palsy (DCP). Methods: Ten participants with DCP, 6–21 years old, users of a head/foot steering system were included. Dystonia and choreoathetosis were assessed using the Dyskinesia Impairment Mobility Scale (DIMS), heart rate (HR) was used to assess the exercise load of the tasks on the participants, and the accelerometry-based activity index (AI) to measure the physical activity intensity and energy expenditure during mobility task performance. Results: Neck- and distal arm dystonia showed significant correlations with HR (0.64 <  r s  < 0.77; 0.009 <  p  < 0.048), whereas neck- and proximal arm choreoathetosis with AI (0.64 <  r s  < 0.76, 0.011 <  p  < 0.044). Total-body AI was strongly correlated to the AI of the arms (0.66 <  r s  < 0.90,  < 0.001 <  p  < 0.038), but not to the AI of the head. Conclusions: During PW mobility tasks, dystonia is associated to exercise load and choreoathetosis to physical activity intensity and energy expenditure. Findings highlight the difficulties in measuring exercise load and activity intensity in PW users with DCP due to the involuntary hypertonic and/or hyperkinetic hallmark of the movement disorders. Nevertheless, a relaxed surrounding with minimal distractions during PW training may increase learning efficiency. Future studies with a bigger sample size are highly recommended to fully establish the relationship between the variables and to allow generalizability of results. Implications for rehabilitation: Dystonia is positively related to heart rate during powered mobility, which may be explained by the hypertonic hallmark of dystonia causing an increase in exercise load. Choreoathetosis is positively related to the physical activity index during powered mobility where the hyperkinetic hallmark of choreoathetosis may lead to an increase in physical activity intensity and energy expenditure. Arm overflow movements are the component which contribute the most to total-body activity index, thus, minimizing these movements may lower the overall energy expenditure during powered mobility. Mobility training in a relaxed surrounding with minimal distractions and minimized arm overflow movements may lead to a less-demanding powered wheelchair mobility experience and increased learning efficiency.